Achievement goals, fears of failure and perceived coaching climate in Malaysian sepak takraw players / Santhosh Ayathupady Mohanan , Abdul Halim Mokhtar and Mazlan Ismail - Mohanan, Santhosh Ayathupady; Mokhtar, Abdul Halim; Ismail, Mazlan (Faculty of Sports Science and Recreation, 2011)
In tune with the multiple achievement goal framework assumptions (Elliot, 1999; Elliot & McGregor, 2001), the present study examined the relationships among achievement goals, fear of failure and perceived coaching climate in male sepak takraw players. Participants (N = 96) completed questionnaires assessing their achievement goals (AGQ-S; Conroy et al., 2003), fear of failure (PFAI; Conroy, 2001) and a modified version of the AGQ-S for assessing perceived coaching climate. Results revealed that the different achievement goal oriented coaching climates found to be significantly correlated to corresponding achievement goals adopted by athletes with the exception of Performance-avoidance goals. None of the achievement goals were significantly correlated to fear of failure. Age was positively correlated to Performance- avoidance goals while Performance-approach goals were negatively correlated to years of competitive sport participation